2007
DOI: 10.1205/psep07030
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Reaction Screening Using Oscillatory Flow Meso Reactors

Abstract: This paper is concerned with performing laboratory scale alkali-catalyst transesterification for biodiesel reaction and ranking conversion and performance between a stirred tank reactor, and oscillatory flow meso reactors in both batch and continuous mode. The results show that a comparative conversion can be achieved for the same reaction conditions, thereby demonstrating that batch and continuous meso reactor configurations can be used for a high throughput screening biodiesel reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…OBRs have been previously used to study biodiesel production at pilot scale [22] and mesoscale [23]. The results showed that the yield of methyl ester in these reactors was similar to that obtained in batch reactor, but at considerably shorter residence times.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…OBRs have been previously used to study biodiesel production at pilot scale [22] and mesoscale [23]. The results showed that the yield of methyl ester in these reactors was similar to that obtained in batch reactor, but at considerably shorter residence times.…”
Section: Introductionmentioning
confidence: 66%
“…At these oscillation conditions, vortices are generated and fully developed after each cavity baffles due to the interactions between oscillatory flow and baffles [21]. Zheng et al [23] also found that good mixing and therefore high conversion were achieved high oscillation conditions, i.e. Re o N 107 and St b 0.2.…”
Section: Central Sharp-edged Bafflesmentioning
confidence: 96%
See 1 more Smart Citation
“…An oscillatory motion is superimposed upon the net flow of the process fluid, creating flow patterns conducive for efficient heat and mass transfer, whilst maintaining plug flow regime [52]. In addition, each baffle essentially behaves as a stirred tank that lead to excellent mixing and suspension by creating vortices between orifice baffles and oscillating fluid [53]. Designing a biodiesel reactor especially when heterogeneous catalysts are used due to the presence of three immiscible phases (oil-alcohol-catalyst) at the initial stage of reaction.…”
Section: Oscillatory Flow Reactor For Transesterification Reactionmentioning
confidence: 99%
“…Microreactors have channels with hydraulic diameter (DH) between 1 μm and 100 μm, while mesoreactors have DH channels between 100 μm and 1 mm [8]. Several micro-and mesofluidic systems were developed and characterized [12][13][14][15], such as medical diagnostic devices with integrated biosensors [16], circulating tumor cell capture systems [17], gradient concentration generators [18], photocatalytic water purification [19], and organic and inorganic synthetic flow reactors [9]. Despite good results, the main disadvantage of small-scale reactors is the relatively high cost combined with the low output of a single reactor and the unfeasibility of production on a commercial scale [20].…”
Section: Introductionmentioning
confidence: 99%